Study on the Medication Rules of Traditional Chinese Medicine (TCM) in Treating Hepatitis B Cirrhosis in the Compensated Stage Based on Data Mining - Chang, Jialin; Dong, Xuelian (Journal of Contemporary Medical Practice, 2025)
Objective: To apply data mining techniques to study the medication rules of Traditional Chinese Medicine (TCM) in the treatment of compensated hepatitis B cirrhosis. This research aims to provide clinical insights for the further development of TCM treatment for compensated hepatitis B cirrhosis. Methods: Using the keywords “hepatitis B cirrhosis compensated stage,” “liver involvement,” and “Traditional Chinese Medicine,” searches were conducted on platforms such as CNKI and Wanfang Database. Articles published from January 2008 to 2023 related to the compensated stage of liver cirrhosis were selected to create a database. The included TCM prescriptions were then analyzed for frequency, association rules, and clustering using software tools like Excel 2021, SPSS Modeler 18, and SPSS 26.0. Results: A total of 44 prescriptions comprising 158 herbal medicines were selected. The five most frequently used herbs were Fuling (Poria), Danshen (Salvia miltiorrhiza), Chaihu (Bupleurum), Baishao (Paeonia lactiflora), and Baizhu (Atractylodes macrocephala). Conclusion: This study summarizes the medication rules for the treatment of compensated hepatitis B cirrhosis, aiming to standardize clinical medication practices.